The Imperforate Anus Psychosocial Questionnaire (IAPSQ): Its construction and psychometric properties - Christensson Kyllike; Brodin Ulf; Nisell Margret; Rydelius Per-Anders (Child and Adolescent Psychiatry and Mental Health, 2009)
Abstract The origin of the present study was to develop the liaison work between the disciplines of child and adolescent psychiatry and paediatric surgery and nursing, so as to improve the quality of treatment and care of a group of children with imperforate anus (IA) and their families. Imperforate anus is a congenital disease involving a deformity of the anorectum. The early surgery and invasive follow-up treatment associated with IA may affect the child psychosocially, including the child-parent relationship. By developing and testing a questionnaire for children born with anorectal anomalies, a tool for measuring psychosocial functioning can be realized. Methods First, a literature review on "Imperforate Anus" was performed. Second, an exploratory interview study was conducted with patients/adolescents with IA and their parents. The findings from these interviews were the foundation for construction of the questionnaire. The Imperforate Anus Psychosocial Questionnaire (IAPSQ) was tested and revised three times before its completion. It contains 45 items on Likert scales. A total of 87 children completed the IAPSQ: 25 children with IA and two comparison groups. Face and content validity were considered. The Rasch approach, an item response theory model, was used to evaluate the psychometric properties of the IAPSQ, where item difficulty and person ability are concurrently approximated. Results The findings of the Rasch analysis revealed that the psychological dimension was reasonable, and that person reliability (0.83) was moderate and item reliability (0.95) was sufficient. The social dimension showed satisfactory item reliability (0.87). The person reliability (0.52) of the social dimension was weak. Content validity seemed to be established and construct validity was recognized on the psychological dimension. Conclusion The IAPSQ provides a reasonably valid and reliable measure of psychosocial functioning for clinical use among children with IA, although some revisions are suggested for the next version of the IAPSQ. By using the Rasch model, we discovered that specific items should be discarded and other items should be reformulated to make the questionnaire more "on target". The social dimension has to be expanded with further items to reasonably capture a social dimension.